Pendampingan Pelaksanaan Pembelajaran Berbasis Proyek (Teaching Factory) Di SMK N 1 Alian Kebumen - Mukhtar, Agus; Hermana, Rifki; Burhanudin, Aan; Ma’mun, Hisyam (CV. IRA PUBLISHING, 2023)
Project-based learning is active learning that can encourage students to think more critically and creatively. The project-based learning process at SMK N 1 Alian Kebumen has been implemented by involving class X, XI and XII students to directly participate in teaching factory workshops to handle consumers. Students' filling out the tracer study form has experienced a significant increase of 100% after the mentoring process and the number of partner industries carrying out teaching industry activities has also increased by 100%.